CUSTOMER SATISFACTION AS THE MEDIATING INFLUENCE OF SERVICE RECOVERY, PERCEIVED QUALITY, AND PRICE FAIRNESS ON INDIHOME TRIPLE PLAY SERVICES TO CUSTOMER LOYALTY - Sofiana, Helmi; Prihandono, Dorojatun (Management Analysis Journal, 2019)
The development of telecominications business is currently growing rapidly which makes many telecommunications companies compete to provide the best service to customers, so they are not eliminated from competition. This study aims to examine how the effect of service recovery, perceived quality, and price fairness on customer loyalty through customer satisfaction as an intervening variable. The population in this study were the consumers of indiHome  Datel Purbalingga. The samppling technique that is used is the purposive sampling method, samples that can be taken with an Slovin formula. The method of the data collection used in this study is documentation and questionnaires. Partial analysis and path analysis using the IBM SPSS 16 program is used as data analysis. The results of the study show that the service recovery and customer satisfaction has a positive and significant direct influence on the costumer loyalty. However, perceived quality and price fairness do not have a direct and  significant influence on the  customer loyalty. Path analysis shows that customer satisfaction can mediate service recovery, perceived quality, and price fairness on the customer loyalty. The suggestions for companies is to optimize their service in terms of improvemment to network hardware and software so that there is no interference with indiHome triple play services. For  further researchers tp examine different subjects and add other variabels that can affect customer loyalty.